Bödewadt flow and heat transfer of dusty fluid with Navier slip - Turkyilmazoglu, M. (Archives of Mechanics, 2022)
The current work deals with two-phase flow and heat transfer induced by a mixture of fluid and dust particles revolving with a constant angular velocity above a slippage planar wall. Interaction of the solids with the fluid through an interaction force while rotating above the surface is formulated through a similarity system of equations akin to the Bödewadt flow in the absence of suspended particles. Although the velocity fields of fluid and solid are strictly coupled, the heat fields are decoupled from the velocity fields, but they are still in contact with each other due to the coupling of fluid and particle temperatures. The dusty fluid flow character is simulated numerically to capture the fluid and dust phase behaviors. The momentum and thermal layers are resolved in the presence of wall slip mechanism. Illustrative and quantitative results are eventually presented reflecting the physical features of particles and fluid at any stage of interaction during the rotary motion. It is revealed that the wall slip mechanism can be effective enough to alter the usual Bödewadt flow phenomenon.